Issues and Performance in the Pennsylvania Workers' Compensation System - Greenberg, Michael D. (RAND Corporation, 2008)
Examines the performance of Pennsylvania's workers' compensation system, focusing on benefits and compensation, workplace safety, medical care, and dispute resolution. The authors find that the system performs fairly well relative to other states, but that it faces challenges in improving safety and in dealing with rising health care costs. The authors discuss future policy options, emphasizing the need for more and better performance data.